Degree of vision impairment influence the fight outcomes in the Paralympic judo: a 10-year retrospective analysis - Mashkovskiy, E.; Magomedova, A.; Achkasov, E. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: In the International Blind Sports Federation (IBSA) judo Sports Classes B1, B2, and B3 compete against each other within weight- and gender-specific categories. B1 athletes are totally blind, whereas B2 and B3 are partially sighted. The aim of this study was to examine the impact of the degree of vision impairment on fight outcomes. METHODS: We analyzed 1936 fights from official competitions and compare win ratio in fights between discordant Sports Classes. RESULTS: B1 won B2 ratio was 34.8%, B1 won B3 ratio was 36.5%, B2 won B3 ratio = 50.6%. The B1 percent of IBSA judo athletes decreased from 25.9% in 2007 to 19.4% in 2016, while the total number of participants increased over this period. CONCLUSIONS: These findings confirm that blind athletes have fewer chances to win a fight in IBSA Judo and become a member of National Team. Loss of vision functions affects movement coordination, balance, and emotional state, which are important for martial arts and may explain why B1 athletes are more likely to lose competitions against either B2 or B3. Creation of the evidence-based and sport-specific classification system and/or improvement of the technical rules are necessary for fair IBSA Judo competitions.